A three-dimensional integrated nanogenerator for effectively harvesting sound energy from the environment. Issue 9 (17th February 2016) - Liu, Jinmei; Cui, Nuanyang; Gu, Long; Chen, Xiaobo; Bai, Suo; Zheng, Youbin; Hu, Caixia; Qin, Yong
Abstract : A three dimensional integrated triboelectric nanogenerator is successfully fabricated to effectively harvest sound energy, and it could be directly used as a power source for the electrophoresis process in a noisy environment. Abstract : An integrated triboelectric nanogenerator (ITNG) with a three-dimensional structure benefiting sound propagation and adsorption is demonstrated to more effectively harvest sound energy with improved output performance. With different multifunctional integrated layers working harmonically, it could generate a short-circuit current up to 2.1 mA, an open-circuit voltage up to 232 V and the maximum charging rate can reach 453 μC s −1 for a 1 mF capacitor, which are 4.6 times, 2.6 times and 7.4 times the highest reported values, respectively. Further study shows that the ITNG works well under sound in a wide range of sound intensity levels (SILs) and frequencies, and its output is sensitive to the SIL and frequency of the sound, which reveals that the ITNG can act as a self-powered active sensor for real-time noise surveillance and health care. Moreover, this generator can be used to directly power the Fe(OH)3 sol electrophoresis and shows great potential as a wireless power supply in the electrochemical industry.